2013
DOI: 10.1111/fwb.12180
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning of leaves by solar radiation and anoxia affects microbial colonisation and rate of leaf mass loss in an intermittent stream

Abstract: Summary Seasonal flow intermittence in streams often coincides with early leaf abscission of riparian vegetation due to water stress. When accumulated on dry stream beds or in remaining pools, leaves are exposed to solar radiation or fermentation processes, respectively. However, very little information exists on how these preconditioning processes could affect leaf decomposition when stream flow has recovered. We simulated natural preconditioning of leaves by irradiation with UV‐VIS fluorescent lamps and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…Some studies have shown that during flow reduction, the communities of aquatic hyphomycetes can experience a shift in fungal richness and composition and alterations in their enzymatic activity, such as summer drying conditions inhibiting lignocellulolytic enzyme activities [10,15,16]. These changes in the communities of aquatic hyphomycetes coupled to changes in the abiotic conditions of streams under flow reduction (e.g., decreasing the dissolved oxygen content and increasing the water temperature and conductivity) are expected to affect organic matter decomposition and the feeding links to higher trophic levels [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that during flow reduction, the communities of aquatic hyphomycetes can experience a shift in fungal richness and composition and alterations in their enzymatic activity, such as summer drying conditions inhibiting lignocellulolytic enzyme activities [10,15,16]. These changes in the communities of aquatic hyphomycetes coupled to changes in the abiotic conditions of streams under flow reduction (e.g., decreasing the dissolved oxygen content and increasing the water temperature and conductivity) are expected to affect organic matter decomposition and the feeding links to higher trophic levels [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Leaching loss during the initial stages of decomposition essentially sets the trajectory of mass loss in aquatic ecosystems (Treplin & Zimmer, 2012), and leaves in upstream sites lost significantly more mass due to leaching during the initial 24 h of the study compared to the other sites. Previous work in intermittent systems has demonstrated that exposure to dry conditions and solar radiation appeared to be a more important control over leaching in leaves that are inconsistently wet (Fellman, Petrone & Grierson, 2013), while these same conditions negatively impact microbial degradation and overall mass loss on drier material (Bruder, Chauvet & Gessner, 2011;Dieter et al, 2013).…”
Section: Influence Of Water Availabilitymentioning
confidence: 99%
“…eutrophication, mass mortality of aquatic organisms) in downstrean receiving waters and groundwater (Baldwin & Mitchell, 2000;Bernal et al, 2013;Cavanaugh, Richardson, Strauss, & Bartsch, 2006;Hladyz et al, 2011;Ocampo, Oldham, Sivapalan, & Turner, 2006). Substrate moisture content and variability in associated microbial communities can potentially be responsible for the unexplained part of the variance in the leachates, due to their effect on decomposition rates of accumulated CPOM, nutrient processing in sediments, release of DOM upon rewetting, and its modification by microbial communities (Abril et al, 2016;Arce et al, 2015;Dieter, Frindte, Krüger, & Wurzbacher, 2013;McIntyre, Adams, Ford, & Grierson, 2009;Meisner, Leizeaga, Rousk, & Bååth, 2017).…”
Section: Environmental Variables Correlated With Release Of Nutrienmentioning
confidence: 99%